The impact of local tape databases on the library: The M(I)das touch - Bakowski, V.B.; Moeckel, L.E. (Online (Wilton, Connecticut), 1990)
There is no abstract available for the item entitled The impact of local tape databases on the library: The M(I)das touch.
Keywords: dept.ils; ⛔ No DOI found